Escherichia coli strains isolated from the uteri horn, mouth, and rectum of bitches suffering from pyometra: virulence factors, antimicrobial susceptibilities, and clonal relationships among strains - Agostinho, Juliana M. A. [UNESP]; Souza, Andressa de [UNESP]; Schocken-Iturrino, Ruben P. [UNESP]; Beraldo, Lívia G. [UNESP]; Borges, Clarissa A. [UNESP]; Avila, Fernando A. [UNESP]; Marin, José M. (International Journal Of Microbiology, 2014)
Pyometra is recognized as one of the main causes of disease and death in the bitch, and Escherichia coli is the major pathogen associated with this disease. In this study, 70 E. coli isolates from the uteri horn, mouth, and rectum of bitches suffering from the disease and 43 E. coli isolates from the rectum of clinically healthy bitches were examined for the presence of uropathogenic virulence genes and susceptibility to antimicrobial drugs. DNA profiles of isolates from uteri horn and mouth in bitches with pyometra were compared by REP, ERIC, and BOX-PCR. Virulence gene frequencies detected in isolates from canine pyometra were as follows: 95.7% fim, 27.1% iss, 25.7% hly, 18.5% iuc, and 17.1% usp. Predominant resistance was determined for cephalothin, ampicillin, and nalidixic acid among the isolates from all sites examined. Multidrug resistance was found on ∼ 50% pyometra isolates. Using the genotypic methods some isolates from uteri, pus, and saliva of the same bitch proved to have identical DNA profiles which is a reason for concern due to the close relationship between household pets and humans.